2016
DOI: 10.7307/ptt.v28i4.1916
|View full text |Cite
|
Sign up to set email alerts
|

Development of Urban Driving Cycle with GPS Data Post Processing

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…For installed measuring systems, we can connect to the vehicle's On-Board Diagnostic (OBD) computer with Controller Area Network (CAN bus) communication, and read data, usually velocity and distance travelled, but also collect other information such as engine performance and fuel consumption [31] [34] [35] [39] [43]. If the vehicle cannot be fitted with a device, for example on a motorcycle, because of the size of the instrument is too large, then a mobile device can be used to measure [33], for example, a handheld GPS receiver [31] [35] or if we use multiple vehicles, and it is not necessary to make more measurement in the same time, we can also move the device [41].…”
Section: Hardware and Software Requirements 21 Hardware For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For installed measuring systems, we can connect to the vehicle's On-Board Diagnostic (OBD) computer with Controller Area Network (CAN bus) communication, and read data, usually velocity and distance travelled, but also collect other information such as engine performance and fuel consumption [31] [34] [35] [39] [43]. If the vehicle cannot be fitted with a device, for example on a motorcycle, because of the size of the instrument is too large, then a mobile device can be used to measure [33], for example, a handheld GPS receiver [31] [35] or if we use multiple vehicles, and it is not necessary to make more measurement in the same time, we can also move the device [41].…”
Section: Hardware and Software Requirements 21 Hardware For Data Collectionmentioning
confidence: 99%
“…That is why GPS is usually used as a supplement (taking into account altitude values, identifying stopping points, etc.) [35] [47] [48] or checking and correcting the values measured with on board instrument [32] [39] [43]. They can also be used to determine the nature of travel (downtown, suburban, express) or to connect the result of measuring to Geographic Information System (GIS) software [42] [43] [49].…”
Section: Hardware and Software Requirements 21 Hardware For Data Collectionmentioning
confidence: 99%
“…Besides, more research for other cases than Europe and China would be useful to create multi-regional models or models across affiliated cities such as the C40 Cities [35]. Since international standardized driving cycles can considerably differ from the uniqueness of local driving patterns [36][37][38], there is a need to estimate energy consumption and to analyze driving cycles for various cases.…”
Section: Utilization Of Large Datasets In Energy Researchmentioning
confidence: 99%
“…However, in almost all previous studies, the selected parameters mainly reflect the driving characteristics, without parameters reflects well vehicle emission characteristics as vehicle specific power (VSP) parameter [8,12]. In addition, most of previous studies often use driving cycle parameters following the experience of previous studies without presenting an explanation of their choice, as in [7], [13], [15], [9] and so on. Meanwhile, the study of Torp et al (2013) showed that on the different data sets, selected parameters could be very different although the data mining method are the same.…”
Section: Introductionmentioning
confidence: 99%